Effectiveness of intermittent theta burst stimulation to enhance upper extremity recovery after stroke: a randomized controlled study - Kolbaşı, Esma Nur; Ersöz Hüseyinsinoğlu, Burcu; Özdemir, Zeynep; Bayraktaroğlu, Zübeyir; Soysal, Aysun (My University, 2024)
Objective: To first investigate the effectiveness of modified Constraint-Induced Movement Therapy (mCIMT) in low-functioning patients with stroke (PwS). Second, we aimed to investigate the efficiency of intermittent theta-burst stimulation (iTBS), applied on intermittent days, in addition to the mCIMT in PwS. Design: Randomized, sham-controlled, single-blinded study. Setting: Outpatient clinic. Participants: Fifteen PwS (age 66.3 ± 9.2 years (mean ± SD); 53% female) who were in the first 1-12 months after the incident were included in the study. Interventions: PwS were divided into 3 groups: 1) mCIMT alone, 2) mCIMT + sham iTBS, and 3) mCIMT + iTBS. Each group received fifteen sessions of mCIMT (1 hour/session, 3 sessions/week). iTBS was applied with 600-pulses on impaired M1 prior to mCIMT. Main outcome measures: Upper extremity (UE) impairment was assessed with the Fugl-Meyer Test (FMT-UE), while the motor function was evaluated with the Wolf-Motor Function Test (WMFT). Motor Activity Log-28 (MAL-28) was used to evaluate the amount of use (AUS) and how well (HWS) the impaired UE movements. Results: With-in-group analysis revealed that all groups had statistically significant improvements based on the FMT-UE and MAL-28 (p<0.05). However, the performance time and arm strength variables of WMFT were only increased in the mCIMT + iTBS group (p<0.05). The only between-group difference was observed in the intracortical facilitation in favor of the mCIMT + iTBS group (p<0.05). The effect size of iTBS was f=0.18. Conclusion: Our findings suggest that mCIMT with and without the application of iTBS has increased the UE motor function in low-functioning PwS. iTBS applied on intermittent days may have additional benefits as an adjunct therapy for facilitating cortical excitability, increasing the speed and strength of the impaired UE as well as decreasing disability.
Keywords: Stroke; Motor-Evoked Potentials; Neurological Rehabilitation; Transcranial Magnetic Stimulation